Mechanistic evaluation of antiarthritic and anti-inflammatory effect of campesterol ester derivatives in complete Freund’s adjuvant-induced arthritic rats - Nazir, Sarwat; Ahmad, Ishtiaq; Mobashar, Aisha; Sharif, Ali; Shabbir, Arham; Chaudhary, Waqas Ashraf (Frontiers in Pharmacology, 2024)
Background: Current therapies for RA have limitations and side effects, leading to a growing need for safer treatment options. Natural compounds from plants are gaining attention for their therapeutic benefits and fewer side effects. One such compound is the campesterol derivative, a steroid derivative occurring in plants. Studies have shown that this derivative has anti-inflammatory properties and can impact the expression of pro-inflammatory factors. The primary objective of this study was to explore and assess the potential therapeutic effects of Campesterol Ester Derivatives (CED) utilizing a rat model of arthritis induced by Complete Freund's Adjuvant (CFA).The rats were divided into specific experimental groups and treated with either CED or piroxicam (as a positive control) for a duration of 28 days. We determined the effects of CED on various parameters including paw edema, thermal hyperalgesia, and mechanical allodynia at different time points. Furthermore, serum levels of inflammatory cytokines, oxidative stress markers and histological analyses were performed. Additionally, mRNA expression levels of inflammatory markers, both pro-inflammatory (such as TNF-α, NF-κB, IL-6, COX-1, COX-2, and IL-4) and antiinflammatory were analyzed.In the arthritic rat model, CED exhibited significant anti-inflammatory effects and resulted in a notable reduction in paw edema levels compared to the control group. Histopathological examination of the treated rats' paws confirmed a decrease in inflammation and tissue damage, including reduced pannus formation and bone erosion. Importantly, there were no observable signs of damage to the liver and kidneys following CED treatment, indicating its safety profile and potential for organ protection. At the molecular level, CED treatment downregulated mRNA expression levels of pro-inflammatory markers, indicating its ability to suppress inflammation. Conversely, certain anti-inflammatory markers were upregulated following CED treatment, suggesting a positive influence on the immune response. The positive effects of CED were not limited to joint inflammation; it also showed systemic benefits by positively influencing hematological and biochemical parameters.CED demonstrated promising therapeutic potential as an anti-inflammatory intervention for arthritis in the experimental rat model. Its ability to reduce inflammation, protect tissues, and improve organ function indicates its multifaceted benefits.